Global pc5 Pulsations During Strong Magnetic Storms: Excitation Mechanisms and Equatorward Expansion - Stepanova, M (European Geosciences Union, 2014)
The dynamics of global Pc5 waves during the magnetic storms on 29-31 October 2003 are considered using data from the trans-American and trans-Scandinavian networks of magnetometers in the morning and post-noon magnetic local time (MLT) sectors. We study the latitudinal distribution of Pc5 wave spectral characteristics to determine how deep into the magnetosphere these Pc5 waves can extend at different flanks of the magnetosphere. The wave energy transmission mechanisms are different during 29-30 October and 31 October wave events. Further, we examine whether the self-excited Kelvin-Helmholtz instability is sufficient as an excitation mechanism for the global Pc5 waves. We suggest that on 31 October a magnetospheric magnetohydrodynamic (MHD) waveguide was excited, and the rigid regime of its excitation was triggered by enhancements of the solar wind density. The described features of Pc5 wave activity during recovery phase of strong magnetic storm are to be taken into account during the modeling of the relativistic electron energization by ultra-low-frequency (ULF) waves.©Author(s) 2014.